Imidazole modified acrylate-containing photocured hydrogels for the efficient removal of malachite green dye from aqueous solutions - ÇAKMAKÇI, EMRAH; AYDIN URUCU, OYA (WILEY, 2021)
In this work, we aimed to prepare a simple and an efficient adsorbent for the removal of toxic, cationic dye; malachite green (MG). We reviewed many previous studies and designed our adsorbent based on the rationale that (1) acidic groups containing monomers which are capable of making hydrogen bonds (or electrostatic interactions) with MG are very effective in adsorption and (2) pi-pi stacking enhances the adsorption capacity. We first synthesized an imidazole-acrylate adduct and used it for the preparation of photocured hydrogels. The imidazole-acrylate adduct was characterized by H NMR and FTIR spectroscopy. The effect of experimental conditions on the MG adsorption properties of the hydrogels such as the effect of pH, time and MG concentration were also investigated. Under the optimum conditions (pH = 6 and 220 min contact time) at room temperature, the maximum adsorption capacity was found as high as 714.28 mg/g. The results showed that the adsorption process of the optimum hydrogel, which can be used 4 times without a significant loss in its adsorption capacity, fits the Langmuir isotherm model. The hydrogel adsorbent displayed good selectivity and reusability.
Keywords: adsorption; applications; functionalization of polymers; photopolymerization; radical polymerization; ADSORPTION CHARACTERISTICS; ACTIVATED CARBON; SELECTIVE ADSORPTION; HIGHLY EFFICIENT; SULFONIC-ACID; NANOCOMPOSITES; NANOPARTICLES; COMPOSITE; CAPACITY; KINETICS